Penerapan Metode User Centered Desaign Untuk Aplikasi Penjualan Berbasis Website - Imam Hidayat; Theofilus Herly H.S.; Angelina Hadriani (CV. Multi Kreasi Media, 2025)
In the digital era that continues to develop, competition in the business world is getting tighter because all competitors are starting to use sophisticated technology to advance their business, with the ease of the internet and public knowledge of technology in almost all circles. This phenomenon also affects the sustainability of a business, in this case also Gerry's gym. Gerry's gym is a sports place that also sells muscle supplements. Currently it has problems in business management and marketing management because it is still not computerized. Product and sales management is often ineffective and inefficient, and security often does not match incoming and outgoing data, of course this is a point that must be addressed immediately for the continuity of the business. This research aims to design and develop a website-based inventory information system by applying the User Centered Design (UCD) method as the method used for the application. This system is designed to increase the accuracy of inventory recording, make it easier to monitor incoming and outgoing goods, and provide a user-friendly interface to minimize operational errors and of course improve marketing. By implementing the UCD method, users can interact with the system according to their habits without needing to make significant adjustments. It is hoped that this system can provide a more systematic. structured and computerized solution in managing supplement stock at Berry Gym, so as to increase efficiency and consumer satisfaction.